Mixed Education and Quality Standard in the University Teaching: A Theoretical Study - Mohammad Omar AL- Momani; Elham Mahmoud Rababa (Indonesian Journal of Educational Research and Technology, 2022)
This study seeks to achieve the following objectives: (i) Introducing e-learning and blended learning, (ii) Introduction to university education, (iii) The study focused on the concept of total quality in education and standards and quality assurance requirements for blended learning, (iv) The study focused on highlighting the criteria for the success of blended learning and its benefits, (v) The study identified obstacles to the application of blended learning, (vi) Preparing a proposed design for the blended learning program. We adopt the descriptive-analytical method in collecting opinions, information, facts, and concepts related to the axes of the study, to build an integrated knowledge system, and to benefit from it in presenting what is referred to about the aspects related to the concept of blended learning, its application, quality assurance, success criteria, and benefits in the educational process. We hope that this study can give information for Mixed Education and Quality Standard in the University Teaching.